House Dust Mite Fauna in the Klang Valley, Malaysia - Mariana, A.; Ho, T.M.; Sofian-Azirun, Mohd; Wong, A.L. (SEAMEO Regional Tropical Medicine and Public Health Network, 2000)
Allergy to house dust mites (HDM) is an important cause of asthma and rhinitis in Malaysia. This study was carried out to evaluate the dust mite fauna in the Klang Valley. Dust samples were collected from 20 houses from March 1994 to February 1995. Thirty-three dust samples from mattresses were examined monthly for the occurrence of HDM. A total of 22 species in 9 families of HDM was identified. The most common and densely populated species was Blomia tropicalis with an average density of 8,934 mites/g of dust. Dermatophagoides pteronyssinus was the next in abundance, followed by Malayoglyphus intermedius. All houses surveyed were found to be infested with HDM and every house had at least 6 species of HDM. B. tropicalis and D. pteronyssinus were found in all mattresses. HDM in the Klang Valley were found to be highly prevalent and present in high densities. In this study, counts of D. pteronyssinus was found to exceed the proposed exposure threshold of 500 mites/g dust, for triggering acute asthma. Although counts of B. tropicalis exceeded D. pteronyssinus, no conclusion could be made because there is currently no exposure threshold for triggering acute asthma, for this species. Monthly distribution of B. tropicalis and D. pteronyssinus showed 2 peaks and 4 peaks, respectively. The major peak for D. pteronysinus was in January 1995 whereas for B. tropicalis, the major peak was more variable and occurred between November 1994 to January 1995. Both the species showed minor peak in April 1994.